Membangun Komunikasi antara Agama dan Pembangunan - Abdul Aziz Ma’arif (Jurnal Iman dan Spiritualitas, 2022)
Development communication, in essence, is communication carried out to implement a country's development plan, so that development messages reach the wider community. Not only communication, religion also has a very strategic role for the success of a development, especially as a spiritual, moral, and ethical basis in the development of a country.